Estudio de la cadena de suministro de alimentos perecederos - Gutierrez Pereyra, Gonzalo Alonso (2021)
The main objective of this article is to carry out a review of the literature focused on the perishable food supply chain management, analyzing the various stages of the chain through different examples, opinions and solutions presented in various research articles. The importance of collaboration between the different parties involved in the supply chain is analyzed, as well as the importance of the flow of information, for which the example of the transport and distribution process of small producers in rural areas is studied. Similarly, proposals and strategies are discussed to extend the useful life of perishable products in production processes, through the study of Kimchi production in a Korean factory, resulting in a proposal to implement processes to extend the life useful of the inputs within the main production process. The challenges faced with respect to the distribution stage to the final consumer are also analyzed, for which the case of supermarkets and the main challenges they face in terms of the supply and sale of perishable products are discussed, for which is proposed the implementation of a dynamic sourcing policy, as opposed to traditional fixed batch sourcing methods. In addition, there are challenges and opportunities regarding the transport of perishable food, for which strategies are proposed that integrate cross docking and route optimization, in order to reduce inventory levels and minimize the risk of losses. Finally, a proposal is presented to characterize the agro-industrial production chains, which are highly complex due to the large number of intermediaries that play a role in them.